2011
DOI: 10.4103/0019-5154.80424
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline cell-rich chondroid syringoma of the finger

Abstract: A mixed tumor is a neoplasm that has microscopic features of both epithelial and mesenchymal differentiation. Such mixed tumors are known as pleomorphic adenomas in the salivary glands, and their cutaneous counterparts are called chondroid syringomas. These tumors commonly occur in the head and neck region of middle-aged men. Hyaline cell–rich chondroid syringoma is a rare benign variant of chondroid syringoma composed of cells with eosinophilic hyaline cytoplasm and plasmacytoid features, the origin of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…Hyaline cell-rich apocrine mixed tumor affects patients between their twenties and seventies with prominent male predilection [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Earlier cases were located in extremities [ 2 , 4 , 5 ], whereas the recent cases also involved the face and neck [ 6 , 8 , 9 ], in addition to extremities [ 7 , 8 , 9 , 10 ]. The sizes of the tumor were approximately up to 25 mm [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyaline cell-rich apocrine mixed tumor affects patients between their twenties and seventies with prominent male predilection [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Earlier cases were located in extremities [ 2 , 4 , 5 ], whereas the recent cases also involved the face and neck [ 6 , 8 , 9 ], in addition to extremities [ 7 , 8 , 9 , 10 ]. The sizes of the tumor were approximately up to 25 mm [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a relatively common cell type, the hyaline cell-rich variant is rare. Approximately 30 cases of hyaline cell-rich apocrine mixed tumor, also known as hyaline cell-rich chondroid syringoma, have been reported to date [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. A previous study reported that 17 out of 18 apocrine mixed tumors with cytologic atypia were a hyaline cell-rich variant [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4,5,7,8] Chondroid syringoma is a benign lesion in most of the cases and recurrence is uncommon. [13] However, malignant forms of chondroid syringoma has rarely been reported. [12,14] Malignant forms of chondroid syringoma are more common in women and predominantly affects trunk and extremities.…”
Section: Discussionmentioning
confidence: 99%
“…The most common locations are the head and neck (Nemoto et al, 2002, Ramaswamy et al, 2011, usually the cheek, nose or skin above the lip (Nemoto et al, 2002). Fewer than 300 cases of chrondroid 644590J HS0010.1177/1753193416644590Journal of Hand Surgery (European Volume)Short report letter research-article2016 Short report letter …”
Section: Dear Sirmentioning
confidence: 99%